HUBUNGAN WAKTU REAKSI DAN DAYA LEDAK OTOT TUNGKAI DENGAN KECEPATAN TENDANGAN SABIT PADA ATLET PUTRA PERGURUAN EMPAT BANDING BUDI CABANG PEKANBARU - Zulfikar Zulfikar; Ramadi Ramadi; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract:This reseach is aim to know the correlation of reaction time between explosive power of legs with speed crescent kick on the men athletes of empat banding budi institution pekanbaru. the form of this research is the correlation study, the population in this research are the athletes of empat banding budi institution pekanbaru, and the sample in this research is consist of six athletes in empat banding budi institusion pekanbaru. the calculation of the first analysis between reaction time (x1) and speed crescent kick (y) where rtable at significant level α (0,05)=0,811, mean rresult (0,482)< rtable (0,811) which mean the hypothesis is rejected and there is a medium correlation between reaction time and speed crescent kick. a second analysis of the correlation between explosive power of legs (x2) and speed crescent kick (y), where rtable at a significant level α (0,05)=0,811 means rresult (0,687)< rtable (0,811), which mean the hypothesis is rejected and there is a strong correlation between explosive power of legs and speed crescent kick. the analysis of three correlation of reaction time (x1) and explosive power of legs (x2) with speed crescent kick (y), where rtable at significant level α (0,05)=0,811, means rresult (0,690)< rtable (0,811), which mean the hypothesis is rejected and there is a strong correlation of reaction time explosive and power of legs with speed crescent kick.Keywords: Reaction Time, Explosive Power Of Legs, Speed Crescent Kick